Revealing Halal Certification Oversight Gaps for MSEs through ArcGIS Dashboard Integration - Syaiful Huda, Imam Arifa'illah; Saadah, Maratun; Sugiarto, Agus; Bin Ibrahim, Mohd Hairy; Prasad, Ravinesh Rohit; Putra, Alfyananda Kurnia; Budianto, Ahyat (Indonesian Journal of Halal Research, 2024)
The Indonesian government has developed a comprehensive halal certification program through the Halal Product Assurance Organizing Body (BPJPH). However, the halal certification recording application requires enhancements due to its lack of data elements pertaining to micro and small enterprises (MSEs) with geographical or location references. Geographic Information System (GIS) technology can serve as a solution for data management in the halal industry, encompassing the management, monitoring and analysis of spatial-temporal and real-time data. This research is aimed at developing geospatial technology for industrial halal management within the scope of MSEs. Methods for developing geospatial technology-based management of halal industry applications use analysis, design, development and evaluation through the ArcGIS online platform developed by Environmental Systems Research Institute (Esri). The findings of this research highlight the potential of geospatial technology in the halal industry. It can be effectively utilized to integrate and comprehensively manage halal industry data on a spatial basis, enabling performance monitoring of MSEs, halal product process assistance and the BPJPH. This technology allows for quick analysis of patterns, distributions, trends, associations and regional comparisons, providing valuable insights. Consequently, geospatial technology can support policy recommendations aimed at accelerating the halal certification process by mapping and analyzing relevant data based on geographic locations, facilitating a better understanding of spatial distribution and relationships within the halal industry. This research successfully develops geospatial technology for managing halal industries within MSEs, enabling comprehensive data integration and spatial analysis. The findings highlight its potential to enhance monitoring, support policy recommendations and accelerate the halal certification process.